The Impact of Birth Order on Parental Expectations: A Focus on The Middle Child Perspective - Devina Maharani; Tri Hayuning Tyas (Developmental and Clinical Psychology, 2025)
Research on birth order, especially concerning middle children, remains limited, leaving a gap in understanding their unique roles and experiences within family dynamics. This study investigates how parental expectations influence middle children's interpersonal relationships, emotional well-being, decision-making, and future aspirations. Employing a qualitative approach, data were gathered through semi-structured interviews with four participants aged 18 to 21. A descriptive phenomenological method was used for data analysis, involving transcription and identification of key quotations relevant to the research questions. The findings reveal diverse parental expectations and their varying impacts on both parent-child and sibling relationships. Middle children express a range of emotional responses and coping strategies, including avoidance, negotiation, and seeking support from parents. The way parental expectations are communicated is shaped by parenting styles, social background, and the extent to which parents understand their children. Moreover, cultural context significantly influences these family dynamics. This study enhances the understanding of middle children's distinct experiences and emphasizes the need to consider birth order and cultural factors when examining parental expectations and family relationships. By shedding light on how expectations are perceived and managed by middle children, the research provides valuable insights for families, educators, and mental health practitioners aiming to support balanced family development.